Another micro-open set in micro topological spaces - Shareef, Hardi A.; Öztürk, Ufuk; Anwer, Deena Ismail (Eximia, 2022)
Topologists have introduced a variety of topologies, as is well known. Fine topology, supra topology, ideal topology, fuzzy topology, .nano topology, and .micro topology are the topologies that exist today, with .micro topology being an enlargement of .nano topology, which has been established by Chandrasekar S. We introduce a new weaker type of .micro semi-open set, called .micro -open sets, and discuss some of its features in this work. Compare it to some other .micro-open sets as well.